FAMILY RESPONSIBILTY OF TABLIGH JAMAAT IN MEDAN NORTH SUMATERA - Jamaluddin, Jamaluddin; Bakar, Abu (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2019)
Tabligh Jamaat in the city of Medan is one of the groups which is different from any other groups; conducting specific Islamic preaching or da’wah by enticing Muslims residing around a mosque for congregational prayers. This activity is one of the implementation namely khuruj teachings they refer to. Practicing khuruj is a form of which they leave their family for some days, weeks and even months, and consequently it seems lacking responsible to their family needs. Hence, this study focused on tracking real understanding of Tabligh Jamaat on family responsibility. The purpose of this study was to assess and explain the understanding Tabligh Jamaat responsibility on their family in Medan based on Islamic law perspective. The research results show that the Tabligh Jamaat percepts that providing a living cost for the family is obligatory for a husband. In this sense, a living cost is divided into two kinds; the first is Jahir living in the forms of clothing, food and shelter. The second is mental living covering religious values of monotheism, jurisprudence, morality and some other points to elevate the family dignity.